Structural changes and molecular mechanism study on the inhibitory activity of epigallocatechin against α-glucosidase and α-amylase - Man, Ziyi; Feng, Yi; Xiao, Jibo; Yang, Hailong; Wu, Xiangting (Frontiers in Nutrition, 2022)
In this work, the inhibition and mechanism of epigallocatechin (EGC) on two key glycoside hydrolases (α-glucosidase, α-amylase) were explored from the molecular structure level. The chemical structure of EGC was characterized by X-ray diffraction, Fourier transform infrared (FTIR) spectroscopy and 1H-NMR spectroscopy. The inhibition of EGC on these two enzymes was colorimetrically determined. The effects of EGC on the chemical structure and spatial configuration of the two enzymes were explored by FTIR spectroscopy, fluorescence spectroscopy and Molecular docking techniques. The results showed that EGC exhibited the inhibition on α-glucosidase and α-amylase by non-competitive manner, and showed a continuous upward trend with the increase of EGC concentration. There was a fluorescence quenching effect of EGC on α-glucosidase and α-amylase. Molecular docking confirmed that EGC can bind to amino acid residues in the enzyme through intermolecular hydrogen bonds and hydrophobic interactions, resulting in the change on the chemical structure and spatial conformation of the enzymes, therefore, decrease the enzyme activity. This result suggested that EGC presents favorable potential to inhibit two key glycoside hydrolases and it would be beneficial to incorporate EGC into functional foods for diabetics.